Subject, Thought and Language in the Early Wittgenstein - Defez Martin, Antoni (Analysis. Journal of Philosophical Research, 2021)
Contrary to the psychological interpretations of the Tractatus, in this writing linguistic normativity and intentionality are presented as an expression of the linguistic action itself, the normativity being fixed by the language itself and its intentionality being an expression of the non-empirical activity of the metaphysical subject.